Effects of physical activity in adults with severe obesity: a systematic review - Thais Regina de Sousa; Wesley Gabriel da Silva Alexandrino; Andressa Souza; Cesar Faundez-Casanova; Mara Jane dos Santos Pascoini; Maise Andréia Mochi Awada; Regiane de Paula; Felipe Merchan Ferraz Grizzo; Karine Oltramari; Greice Westphal-Nardo; Nelson Nardo Junior (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
The primary objective of this research was to identify effective modes of physical exercise to optimize the quality of life and health ofindividuals affected by severe obesity. To conduct this systematic review, the PubMed, Web of Science, and Dimensions databases were consulted. The inclusion criteria encompassed original articles publicly available, written in Portuguese, English, or Spanish, addressing exercise protocols targeted at individuals with severe obesity, aged between 18 and 65 years, and with a body mass index (BMI) equal to or greater than 40 kg/m2. The methodological quality of randomized clinical trials (RCTs) was individually assessed by reviewers based on the Physiotherapy Evidence Database (PEDro) scale. Anthropometric measurements, functional capacity, parameters of physical fitness, and quality of life were employed as performance indicators in the results. A notable heterogeneity was observed in the protocols adopted, encompassing variation in the number of sessions, intervention duration, outcome criteria, and sample size, among other factors. The results indicated that intervention programs for severe obesity, regardless of the training modality, demonstrated effectiveness in reducing various anthropometric parameters and improving biochemical variables. Additionally, these programs encouraged the adoption of a healthier lifestyle by individuals affected by severe obesity.